Searching iron sensors in plants by exploring the link among 2′-OG-dependent dioxygenases, the iron deficiency response and metabolic adjustments occurring under iron deficiency - VIGANI, GIANPIERO; Morandini, Piero; MURGIA, IRENE (Frontiers in Plant Science, 2013)
Knowledge accumulated on the regulation of iron (Fe) homeostasis, its intracellular trafficking and transport across various cellular compartments and organs in plants; storage proteins, transporters and transcription factors involved in Fe metabolism have been analyzed in detail in recent years. However, the key sensor(s) of cellular plant “Fe status” triggering the long-distance shoot–root signaling and leading to the root Fe deficiency responses is (are) still unknown. Local Fe sensing is also a major task for roots, for adjusting the internal Fe requirements to external Fe availability: how such sensing is achieved and how it leads to metabolic adjustments in case of nutrient shortage, is mostly unknown. Two proteins belonging to the 2′-OG-dependent dioxygenases family accumulate several folds in Fe-deficient Arabidopsis roots. Such proteins require Fe(II) as enzymatic cofactor; one of their subgroups, the HIF-P4H (hypoxia-inducible factor-prolyl 4-hydroxylase), is an effective oxygen sensor in animal cells. We envisage here the possibility that some members of the 2′-OG dioxygenase family may be involved in the Fe deficiency response and in the metabolic adjustments to Fe deficiency or even in sensing Fe, in plant cells.